Insight On The Nabhi Marma From Anatomical Aspect: A Systemic Review - Jain, Nishi; Solanki, Nupur Singh (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda focussed mainly on the preventive aspect rather than curative in comparison to other systems of medicine. The concept of Marma in the Ayurveda is pioneer in science of traumatology, which has explored the vulnerable areas of human body. Marma play very important role in surgical procedure by avoiding injury to the adjacent vital point. Every individual must know about the vital parts of our body so that they prevent them from any type of injury. Marma defined as sites where there is conglomeration of Mamsa, Sira, Snayu, Asthi and Sandhi, Prana(life) resides naturally. In between Amashaya and Pakvashaya root of Sira is Nabhi Marma, which is responsible for Sadyahpranahara on trauma. It is Sira Marma. It is Svapanitala in Pramana or Caturangula. Nabhi marma extends from the superior mesenteric vessels appearing between the neck of the pancreas and the third part of the duodenum crossing its anterior surface in median plane (L3 vertebra) to the formation of inferior vena cava from common iliac veins (L5). This includes abdominal aorta as well as inferior vena cava.